2022
DOI: 10.17392/1404-21
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between depression and quality of life after myocardial infarction

Abstract: <p><strong>Aim</strong> <br />To examine the prevalence of depression in patients after acute myocardial infarction (AMI), as well as the relationship between the depression and quality of life.<br /><strong>Methods</strong> <br />The survey was conducted via sociodemographic questionnaire, Beck Depression Inventory (BDI), and Short Form 36<br />Health Survey questionnaire (SF-36). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Research conducted by Oginska-Bulik [32] showed that among patients after MI, people with a type D personality were characterized by a lower quality of life compared to people with an atypical type D personality. Džubur et al [33] showed the in uence of depression on decreased quality of life among post-MI patients. Similar results were obtained by Spanish researchers Upadhyayi et al [34], who observed that depression and poor social support led to impairments in the physical and social domains of QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by Oginska-Bulik [32] showed that among patients after MI, people with a type D personality were characterized by a lower quality of life compared to people with an atypical type D personality. Džubur et al [33] showed the in uence of depression on decreased quality of life among post-MI patients. Similar results were obtained by Spanish researchers Upadhyayi et al [34], who observed that depression and poor social support led to impairments in the physical and social domains of QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by Oginska-Bulik showed that among patients after MI, people with a type D personality were characterized by a lower quality of life compared to people with an atypical type D personality 32 . Džubur et al showed the influence of depression on decreased quality of life among post-MI patients 33 . Similar results were obtained by Spanish researchers Upadhyayi et al, who observed that depression and poor social support led to impairments in the physical and social domains of QoL 34 .…”
Section: Discussionmentioning
confidence: 99%